Řízení správy budov - Maršálek, Ondřej (Vysoké učení technické v Brně. Fakulta stavební, 2025)
Diplomová práce je rozdělena na dvě části, teoretickou a praktickou. Teoretická část práce nejprve popisuje nemovitost v provozní fázi životního cyklu staveb. Poté jsou popsány procesy a nástroje facility managementu a propojení s prvky projektového řízení. Praktická část práce se věnuje popisu řízení správy budov Fakultní nemocnice Brno. Následuje návrh manuálu užívaní a správy budovy Z, který obsahuje časové harmonogramy oprav a revizí, strukturní plán oprav a matici odpovědnosti.

The thesis is divided into two parts, theoretical and practical. The theoretical part of the thesis first describes the real estate in the operational phase of the life cycle of buildings. Then the processes and tools of facility management and the connection with the elements of project management are described. The practical part of the thesis is devoted to the description of building management of the University Hospital Brno. This is followed by a draft manual for the use and management of Building Z, which includes timetables for repairs and revisions, a structural repair plan and a responsibility matrix.
Management of Building Management
Keywords: Řízení správy budov; facility management; projektové řízení; životní cyklus staveb; provozní fáze; údržba budov; správa budov; plán údržby; plán oprav; technologické zařízení; manuál užívání a správy budovy; časový harmonogram; plán revizí; strukturní plán.; Building management; facility management; project management; building life cycle; operational phases; building maintenance; building management; maintenance plan; repair plan; process equipment; building use and management manual; schedule; revision plan; structural plan.